Proposed management of nata de coco production waste with green productivity (Case study in UKM Usaha Tani Lebak) - Friskayani, I Gusti Ayu; Herlina, Lely; Muharni, Yusraini; Kurniawan, Bobby; Ilhami, Muhammad Adha; Anggraeni, Shanti Kirana (Jurnal Teknika, 2024)
UKM Tani Lebak is an industry that processes coconut water into nata de coco. During production, water use could be more efficient. Apart from that, there are also rejected products and production waste that pollute the environment. So, based on this, it is necessary to measure and evaluate productivity and environmental performance. This research aims to determine the value of productivity and the green productivity index (GPI) and to propose alternative improvement solutions to increase productivity and reduce environmental impacts. The method used to solve this problem is green productivity, starting with calculating material balance during production, then creating green value stream mapping and calculating GPI. The calculation results show that the productivity value moved from 1.335 to 1.336. UKM Tani Lebak can use three alternative solutions to increase productivity while reducing environmental impacts. The best alternative is to combine the neutralization and washing processes, which produces a GPI from 0.6882 to 0.927. This value shows a better ratio of productivity to environmental impact.